2011
DOI: 10.3109/0886022x.2011.618922
|View full text |Cite
|
Sign up to set email alerts
|

Which Method of GFR Estimation Has the Best Prognostic Value in Patients Treated with Primary PCI: Cockcroft–Gault Formula, MDRD, or CKD-EPI Equation?—A 6-Year Follow-Up

Abstract: CKD is associated with higher mortality after a successful primary PCI during a 6-year follow-up. C-G formula is better than MDRD and CKD-EPI equations at predicting mortality after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
8
11
2
2
Order By: Relevance
“…Nevertheless, the MCQE equation more accurately classified individuals compared with MDRD and CG formulae. Our results extend knowledge from previous studies [1],[2]. Further investigations should be performed to determine whether these costless formulae could be used as an additional validated predictor in this group of patients and hence whether they could be incorporated into clinical practice.…”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, the MCQE equation more accurately classified individuals compared with MDRD and CG formulae. Our results extend knowledge from previous studies [1],[2]. Further investigations should be performed to determine whether these costless formulae could be used as an additional validated predictor in this group of patients and hence whether they could be incorporated into clinical practice.…”
Section: Resultssupporting
confidence: 84%
“…23 A previous prospective cohort study of patients with STEMI followed up during a long time also demonstrated that the Cockcroft-Gault formula was superior than MDRD and CKD-EPI equations at predicting mortality after acute myocardial infarction. 24 Similar results were found in a study including patients with ACS, in which Cockcroft-Gault equation better stratified patients according to their risk of 1-year mortality in comparison to the MDRD-4 or the CKD-EPI equations. 25 In a nationwide registry in Sweden, Cockcroft-Gault equation was better than the MDRD equation in predicting mortality after a myocardial infarction, and seems to be superior for predicting short-and long-term mortality.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, in a recent report from a large registry including patients with heart failure, the Cockcroft‐Gault equation predicted mortality better than the CKD‐EPI and MDRD equations . A previous prospective cohort study of patients with STEMI followed up during a long time also demonstrated that the Cockcroft‐Gault formula was superior than MDRD and CKD‐EPI equations at predicting mortality after acute myocardial infarction . Similar results were found in a study including patients with ACS, in which Cockcroft‐Gault equation better stratified patients according to their risk of 1‐year mortality in comparison to the MDRD‐4 or the CKD‐EPI equations .…”
Section: Discussionsupporting
confidence: 57%
“…The prognostic importance of CKD‐EPI has been evaluated in different settings. In one study in patients with myocardial infarction, CKD‐EPI was inferior to the Cockcroft–Gault equation in predicting mortality, but was a powerful predictor of in‐hospital events in a study of patients with acute coronary syndrome . In a large population of acute myocardial infarction patients with impaired systolic function or signs of heart failure, use of the CKD‐EPI equation improved risk stratification compared with sMDRD .…”
Section: Discussionmentioning
confidence: 99%